Eating Habits Associated with Overweight and Obesity: Case - Control Study in 11-14 year old Adolescents in Hanoi in 2020 - Nguyen Thi Hong Hanh; Tran Thi Thu Hang; Pham Hong Lam; Duong Nam Khanh; Do Hoang Ngoc Ha (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2021)
Eating habits appears to be an important determinant of dietary intake and may consequently influence overweight and obesity. Understanding the relationship between the nutritional status and eating habits is necessary for effective prophylaxis and intervention of overweight/obesity in adolescents. The purpose of this study is to analyze the association of some eating habits with overweight and obesity among adolescents at the age of 11-14 from 9 junior high schools in Hanoi city to help design a model for predicting overweight and obesity from eating habits. A case-control study was conducted on 222 overweight/obese adolescents and 616 normal-weight adolescents (according to International Obesity Taskforce standards, IOTF). Research results indicated that protective factors of overweight and obesity include snacking; snacking at least 2 hours before or after a main meal; consumption of milk and dairy products in snacks; sensory liking for fruit. Risk factors include sensory liking for fat, sensory liking for sweet, sensory liking for fast food, sensory liking for carbonated soft drinks, skipping breakfast, and snacking before bed. The best predictive model of overweight and obesity s built from logistic regression analysis including 8 of the above eating habits with AUC (Area Under the Curve) value of 0.931. Thus, eating habits are closely related to overweight and obesity among 11-14 year-old adolescents in Hanoi. Keywords Eating habits, overweight, obesity, adolescence, risk factor. References [1] A.S. French, M. Story and C.L. Perry, Self-esteem and obesity in children and adolescents: a literature review, Obesity Research 3 (1995) 479-490. https://doi.org/10.1002/j.1550-8528.1995.tb00179.x[2] E.A. Finkelstein, C.J. Ruhm, and K.M. Kosa, Economic causes and consequences of obesity, Annual Review of Public Health 26 (2005) 239-257. https://doi.org/10.1146/annurev.publhealth.26.021304.144628 [3] N.T.H. Hanh, L.T. Tuyet, D.T.A. Dao, Y. Tao, and D.T. Chu, Childhood obesity is a high-risk factor for hypertriglyceridemia: a case-control study in Vietnam, Osong public health and research perspectives 8 (2017) 138-146. https://doi.org/10.24171/j.phrp.2017.8.2.06[4] J.K. Dibaise, and A.E. Foxx-Orenstein, Role of the gastroenterologist in managing obesity, Expert Review of Gastroenterology & Hepatology (Review) 7 (2013) 439-451 https://doi.org/10.1586/17474124.2013.811061[5] P.V.N. Nguyen, T.K. Hong, T. Hoang, and A.R. Robert, High prevalence of overweight among adolescents in Ho Chi Minh City, Vietnam, BMC Public Health 13 (2013) 141-147. https://doi.org/10.1186/1471-2458-13-141[6] T.T.P. Pham, Y. Matsushita, L.T.K. Dinh, T.V. Do, T.T.T. Nguyen, A.T. Bui, A.Q. Nguyen, and H. Kajio, Prevalence and associated factors of overweight and obesity among schoolchildren in Hanoi, Vietnam, BMC public health 19 (2019) 1478-1488. https://doi.org/10.1186/s12889-019-7823-9[7] H.D. Phan, T.N.P. Nguyen, P.L. Bui, T.T. Pham, T.V. Doan, D.T. Nguyen, and H.V. Minh, Overweight and obesity among Vietnamese school-aged children: National prevalence estimates based on the World Health Organization and International Obesity Task Force definition, PloS one 15 (2020) e0240459-e0240478. https://doi.org/10.1371/journal.pone.0240459[8] M. Zalewska, and E. Maciorkowska, Selected nutritional habits of teenagers associated with overweight and obesity, PeerJ 5 (2017) e3681-e3693. https://doi.org/10.7717/peerj.3681[9] K. Sygit, W. Kollataj, M. Gozdziewska, M. Sygit, B. Kollataj, and I.D. Karwat, Lifestyle as an important factor in control of overweight and obesity among schoolchildren from the rural environment, Annals of Agricultural and Environmental Medicine 19 (2012) 557-561. PMID: 23020056. https://journals.indexcopernicus.com/search/article?articleId=2116928[10] N.V. Tuan, Evidence-Based Medicine, Medical publisher, Hanoi, 2008 (in Vietnamese).[11] T.J. Cole, M.C. Bellizzi, K.M. Flegal, and W.H. Dietz, Establishing a standard definition for child overweight and obesity worldwide: international survey, Bmj 320 (2000) 1240-1245. https://doi.org/10.1136/bmj.320.7244.1240[12] L.T. Hop và Huynh Phuong Nam, Assessment of nutritional status using anthropometric variables, Journal of Food and Nutrition Sciences 7 (2011) 1-7 (in Vietnamese).[13] X. Guo, L. Zheng, Y. Li Y, S. Yu, G. Sun, H. Yang, X. Zhou, X. Zhang, Z. Sun, and Y. Sun, Differences in lifestyle behaviors, dietary habits, and familial factors among normal-weight, overweight, and obese Chinese children and adolescents, International Journal of Behavioral Nutrition and Physical Activity 9 (2012) 120-128. https://doi.org/10.1186/1479-5868-9-120[14] J. Yoshida, E. Eguchi, K. Nagaoka, T. Ito, and K. Ogino, Association of night eating habits with metabolic syndrome and its components: a longitudinal study, BMC Public Health 18 (2018) 1366-1379. https://doi.org/10.1186/s12889-018-6262-3[15] L.A. Spence, C.J Cifelli, and G.D. Miller, The role of dairy products in healthy weight and body composition in children and adolescents, Current Nutrition & Food Science 7 (2011) 40-49. https://doi.org/10.2174/157340111794941111[16] R.E. Black, S.M. Williams, I.E. Jones, and A. Goulding, Children who avoid drinking cow milk have low dietary calcium intakes and poor bone health, The American journal of clinical nutrition 76 (2002) 675-680. https://doi.org/10.1093/ajcn/76.3.675[17] I.F.F. Júnior, D.G. Christofaro, J.S. Codogno, P.A. Monteiro, L.S. Silveira, and R.A. Fernandes, The association between skipping breakfast and biochemical variables in sedentary obese children and adolescents, The Journal of pediatrics 161 (2012) 871-874. https://doi.org/10.1016/j.jpeds.2012.04.055[18] R. Rosenheck, Fast food consumption and increased caloric intake: a systematic review of a trajectory towards weight gain and obesity risk, Obesity reviews 9 (2008) 535-547. https://doi.org/10.1111/j.1467-789X.2008.00477.x[19] A. Lampuré, K. Castetbon, A. Deglaire, P. Schlich, S. Péneau, S. Hercberg, and C. Méjean, Associations between liking for fat, sweet or salt and obesity risk in French adults: a prospective cohort study. International Journal of Behavioral Nutrition and Physical Activity 13 (2016) 74-88. https://doi.org/10.1186/s12966-016-0406-6[20] H.C. Hung, K.J. Joshipura, E. Jiang, F.B. Hu, D. Hunter, S.A. Smith-Warner, G.A. Colditz, B. Rosner, D. Spiegelman, and W.C. Willett, Fruit and vegetable intake and risk of major chronic disease, Journal of the National Cancer Institute 96 (2004) 1577-1584. https://doi.org/10.1093/jnci/djh296[21] D.S. Eweis, F. Abed, and J. Stiban, Carbon dioxide in carbonated beverages induces ghrelin release and increased food consumption in male rats: implications on the onset of obesity, Obesity research & clinical practice 11 (2017) 534. https://doi.org/10.1016/j.orcp.2017.02.001[22] M.K. Siddiqui, R. Morales-Menendez, and S. Ahmad, Application of receiver operating characteristics (ROC) on the prediction of obesity, Brazilian Archives of Biology and Technology 63 (2020) e20190736-e20190749. http://dx.doi.org/10.1590/1678-4324-2020190736